ВЛИЯНИЕ ВОЕННЫХ НИОКР НА ИННОВАЦИОННОЕ РАЗВИТИЕ В ГРАЖДАНСКОМ СЕКТОРЕ - Арутюнян, Гаяне (Вопросы государственного и муниципального управления, 2017)
The main route of economic development on an innovative basis implies the efficient implementation of scientific research and development activities (R&D) in a country. However, if economists generally agree that R&D expenses contribute to the technological development of the economy and improve the sectorial structure of industry in favor of highly technological, value adding industries, then the contradictions between scientific viewpoints in debates on the impact of military R&D expenses are of a more acute character. Even in cases where empirical researches reveal the positive interdependence between military R&D expenses and the most important indicators of economic development, the issues regarding their benefit to broad layers of society always remain disputable. The article summarizes analyses of the impact of military R&D on the economy conducted at different times, and coordinates the conclusions drawn. The main directions of impact of military R&D on the economy are presented: security effect, aggregate demand growth effect, aggregate supply growth effect, positive spillover effect, negative spillover effect, and crowding-out effect. In addition, the dynamics of military R&D in Armenia have been studied and certain judgments evaluating their peculiarities are presented.